Cycle time simulation study for cluster tool operation in IC fabrication. (22nd February 2012) - Gupta, Amit Kumar; Sivakumar, Appa Iyer; Lendermann, Peter
A cluster tool basically consists of one or more loadlocks where wafers enter and exit the cluster tool, two or more processing chambers where the processes are performed and one or more handlers that transport the wafers between loadlocks and processing chambers. This paper focuses on understanding the behaviour of a cluster tool system by simulation modelling, experimenting on the model and finding out the factors that influence the tool overall cycle time. The number of deposition chambers, number of robot grippers, clean cycle, MTTF and MTTR are identified as the most important factors for cycle time reduction at cluster tool in semiconductor wafer fabrication.